Review of the Fund's Income Position for FY 2013 and FY 2014. (Policy Papers; Policy Paper, 2013)
This paper reviews the Fund's income position for FY 2013 and FY 2014. The paper updates projections provided at the FY 2013 midyear review and proposes decisions for the current and next financial year. The paper includes a comprehensive review of the Fund's income position as required under the new Rule I-6(4) adopted in December 2011 (see Box 1). Based on this review, no change in the margin for the rate of charge is proposed. The paper is structured as follows: The first section reviews the FY 2013 income position and the main changes from the midyear projections; the second section makes proposals on the disposition of FY 2013 net income, and placement to reserves; the third section discusses the margin on the rate of charge for FY 2014, updates the income projections, and reviews the projected burden sharing adjustments; and the last section reviews special charges.